Ethics of Pharmacy Practice: Ethical Principles Knowledge and Perceived Ethical Practices of Community and Hospital Pharmacists in Nigeria - Okoro, Roland Nnaemeka; Hedima, Erick Wesley; Abdullateef, Siyaka; Aguiyi-Ikeanyi, Chinelo Nneka; Mudenda, Steward (Journal of Pharmacy Practice and Community Medicine)
Background: Professions and occupations are distinguished by ethical obligations and guidelines. The objectives of the study were to assess the ethical principles knowledge and perceived ethical practices of community and hospital pharmacists in Nigeria. Materials and Methods: This cross-sectional survey was conducted among the community and hospital pharmacists in Nigeria. A validated web-based instrument was used for data collection. Study data were initially summarized using descriptive statistics, while ethical principles’ knowledge levels of the community and hospital pharmacists were compared using the Pearson chi-square test. A statistically significant level was set at p < 0.05. Results: Of 300 pharmacists that were approached, 245 completed the survey (response rate = 81.7%). The overall mean knowledge score of the respondents is 2.68 ± 1.49 out of a maximum score of 7 points. Over half (68.2%) of the respondents were accessed for ethical information at their pharmacies, while only 3.3% documented ethical concerns very often. Conclusion: This survey revealed poor knowledge of ethical principles among the respondents. Documentation of ethical concerns was also very poor. Therefore, educational and workplace reorganizational interventions are recommended to promote high-quality pharmaceutical care delivery.
Keywords: Community pharmacists; Hospital pharmacists; Nigeria; Ethics; Pharmacy practice